PENGEMBANGAN MEDIA KOMIK MENGGUNAKAN APLIKASI IBIS PAINT X MATERI MEMBACA CERITA DI KELAS IV SD NEGERI 29 PONTIANAK KOTA - Saputri, Sela; Priyadi, Antonius Totok; Kresnadi, Hery (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is driven by the lack of variety of learning media and limited facilities such as projectors, which causes a lack of media diversity in the fourth grade of SD Negeri 29 Pontianak City. Therefore, by considering these limitations, this research was conducted to develop comic media using the Ibis Paint X application on story reading material as a learning aid. This research is a research and development (RnD) that uses the ADDIE model. The data were obtained from the results of feasibility assessments by experts and practicality by students. Data collection techniques used interviews and questionnaires, with instruments in the form of interview sheets, product feasibility assessment sheets and product practicality assessment sheets. The sample in this study involved 23 fourth grade students of SD Negeri 29 Pontianak City. The results of the product feasibility by experts obtained an overall result of 91% with the category of "very feasible". While the results of the product practicality obtained an assessment of 92% from students included in the category of "very practical". Based on these results, it can be concluded that the comic media using the Ibis Paint X application on the story reading material developed has a positive impact on students with the criteria of being feasible and practical to use.